A fiber-reinforced PET blister sheet
By using a combination of fiber reinforced and functional rubber in PET blister sheets, the shortcomings of PET blister sheets in terms of impact toughness and antibacterial properties are solved, and their mechanical properties and antibacterial properties are significantly improved, which extends the service life and broadens the application range.
Patent Information
- Application Number
- CN202411606682.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-11-12
AI Technical Summary
PET blister sheets have shortcomings in impact toughness and antibacterial properties, and are prone to rupture, wear and erosion by bacteria, resulting in reduced performance and shortened service life.
By using the preparation method of fiber-reinforced PET blister sheet, zirconia fibers are organically modified and combined with polycarbonate diol and functional rubber to form fiber-reinforced components and functional rubber, and added to the PET matrix to improve its mechanical properties and antibacterial properties.
It significantly improves the mechanical properties, impact resistance and antibacterial properties of PET blister sheets. The tensile strength can reach 65.2MPa, the impact strength can reach 16.7KJ/m2, and the antibacterial rate can reach 99.9%, extending the service life and broadening the application range.
Smart Images

Figure CN119220066B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of blister sheets, in particular to a fiber-reinforced PET blister sheet. Background Art
[0002] PET, also known as polyethylene terephthalate, is a thermoplastic, highly crystalline polymer with excellent creep resistance, dimensional stability, good gloss, good tolerance to acids, alkalis, and most solvents, good water, gas, oil, and odor resistance, and good thermoformability and processing properties. It can be processed in a variety of ways and has high flexibility in preparation shape and size. Therefore, it can be used as a preparation material for blister sheets. PET blister sheets are widely used in food packaging, daily chemical products, pharmaceutical industry, industrial products, and advertising decoration industry, etc. Therefore, research and improvement of PET blister sheets are of great significance.
[0003] PET blister sheet also has disadvantages. PET material has poor impact toughness. When subjected to external impact or pressure, it is easy to break or damage. It is more likely to be worn, scratched, and deformed under long-term use, thereby affecting the function of the product and reducing durability. PET material has insufficient antibacterial performance and is easily eroded by bacteria, which will lead to reduced transparency and performance and shortened service life. Patent No. CN108715674B discloses a PET composite material and a preparation method thereof. The PET composite material includes the following raw materials: PET, nano hydroxyethyl methyl cellulose, PPG, and an antioxidant. The PET composite material is prepared by extrusion granulation. The nano hydroxyethyl methyl cellulose can form hydrogen bonds with PET, generate a network structure in space through hydrogen bonds, promote heterogeneous nucleation of PET, improve the crystallinity of PET, and improve the mechanical properties of the PET composite material. However, the patent does not take into account the poor antibacterial performance of the PET composite material, which is easily eroded by bacteria, resulting in performance degradation, and shortened service life of the PET material. Therefore, the present invention provides a PET blister sheet with excellent mechanical properties, impact resistance and antibacterial properties, and broadens the application range of the PET blister sheet. Summary of the invention
[0004] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a fiber-reinforced PET blister sheet.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A fiber-reinforced PET blister sheet comprises the following raw materials in parts by weight: 75-90 parts of PET, 1-3 parts of a compatibilizer, 0.5-2 parts of a lubricant, 5-8 parts of a filler, 3-6 parts of a fiber-reinforced component, and 2-5 parts of a functional rubber.
[0007] Furthermore, the compatibilizer is ethylene-methyl acrylate-glycidyl methacrylate; the lubricant is calcium stearate or zinc stearate; and the filler is talc powder or mica powder.
[0008] Furthermore, the method for preparing the fiber-reinforced component comprises the following steps:
[0009] Step SS1: Disperse the zirconium oxide fiber in N,N-dimethylformamide to form a uniform suspension, introduce nitrogen protection, add a halogenated acid anhydride modifier, dicyclohexylcarbodiimide and 4-dimethylaminopyridine to the suspension, mix evenly, stir for 4-6 hours, filter, wash and dry to obtain modified zirconium oxide fiber;
[0010] Step SS2: Add the modified zirconia fiber to dimethyl sulfoxide, disperse it evenly, introduce nitrogen protection, add polycarbonate diol and alkaline catalyst, mix evenly, increase the system temperature to 70-80°C, react for 5-6 hours, separate the product, wash and dry it to obtain a fiber reinforced component.
[0011] By adopting the above technical scheme, under the action of dicyclohexylcarbodiimide and 4-dimethylaminopyridine, the hydroxyl group on the surface of the zirconium oxide fiber can react with the halogenated acid anhydride modifier, thereby introducing a halogen substituent on the surface of the zirconium oxide fiber, and under the action of an alkaline catalyst, the halogen substituent on the surface of the zirconium oxide fiber can undergo a substitution reaction with the alcohol hydroxyl group in the polycarbonate diol structure to obtain a fiber-reinforced component. The fiber-reinforced component prepared by the present invention takes the zirconium oxide fiber as a matrix, and after organic modification, effectively improves the compatibility problem with the PET matrix, can be uniformly dispersed in the PET matrix, and avoids agglomeration to adversely affect the mechanical properties of the PET matrix. The carboxyl group in the fiber-reinforced component can improve the bonding strength of the interface between the zirconium oxide fiber and the PET matrix, which helps to more effectively transfer the external force to the fiber and improve the mechanical properties of the PET matrix. At the same time, the polycarbonate diol in the fiber-reinforced component can interact with the PET molecular chain, and also has a positive improvement effect on the mechanical properties of the PET matrix. Therefore, the two have the effect of synergistically improving the mechanical properties of the PET blister sheet.
[0012] Furthermore, in step SS1, the halogenated acid anhydride modifier is 3-chlorophthalic anhydride or 4-chlorophthalic anhydride.
[0013] Furthermore, in step SS2, the alkaline catalyst is potassium carbonate or sodium carbonate.
[0014] Furthermore, the preparation method of the functional rubber is as follows:
[0015] Step A: adding carboxyl-terminated polybutadiene acrylonitrile liquid rubber to dimethyl sulfoxide, stirring and mixing evenly, adding dithiothreitol, dicyclohexylcarbodiimide and 4-dimethylaminopyridine, reacting for 4-6 hours, separating the product, and obtaining a modified rubber;
[0016] Step B: Add the modified rubber to tetrahydrofuran, stir and mix evenly, introduce nitrogen protection, add magnolol and photoinitiator, irradiate with ultraviolet light with a wavelength of 352nm and a power of 40W in a dark environment, react for 1-3h, remove the solvent by reduced pressure distillation, and obtain functional rubber.
[0017] By adopting the above technical scheme, under the action of dicyclohexylcarbodiimide and 4-dimethylaminopyridine, the carboxyl group in the carboxyl-terminated polybutadiene acrylonitrile liquid rubber structure can undergo an esterification reaction with the hydroxyl group in the dithiothreitol structure to introduce a thiol group, and then under the irradiation of an ultraviolet lamp and the action of a photoinitiator, the introduced thiol group can undergo a thiol-ene click reaction with the olefinic group in the magnolol structure to obtain a functional rubber. The functional rubber prepared by the present invention contains a large number of flexible segments, which is conducive to balancing the rigidity of the PET matrix molecular chain, avoiding excessive rigidity that reduces the ability to resist deformation and causes fatigue damage, and improving ductility. The functional rubber has a branched structure and can be cross-linked with the PET matrix under the action of a compatibilizer to form a network structure, thereby enhancing the density of the PET matrix. When subjected to external force impact, the functional rubber acts as a stress concentration point to absorb and relieve impact energy, induce shear yield of the matrix, and improve the impact resistance of the PET matrix. In addition, magnolol is introduced into the rubber in a chemical bonding manner, thereby giving the PET matrix excellent antibacterial performance, while also avoiding the problem that small molecule magnolol is easily precipitated, resulting in reduced antibacterial performance and erosion of the PET material by bacteria. The rubber has a long-lasting antibacterial effect and extends the service life of the PET blister sheet.
[0018] Furthermore, in step A, the number average molecular weight of the carboxyl-terminated polybutadiene acrylonitrile liquid rubber is 2500.
[0019] Furthermore, in step B, the photoinitiator is benzoin dimethyl ether or benzoin isopropyl ether.
[0020] A method for preparing a fiber-reinforced PET blister sheet comprises the following steps:
[0021] Step 1: Add PET, compatibilizer, lubricant, filler, fiber reinforcement component and functional rubber into a mixer according to weight, set the mixing temperature to 70-100°C, set the stirring speed to 100-300r / min, stir and mix for 20-50min, and obtain a premixed base material;
[0022] Step 2: Melt and knead the premixed base material at 180-220°C, extrude and granulate to obtain a PET composite material;
[0023] Step 3: Add the PET composite material into a twin-screw extruder, perform melt plasticization, extrusion, rolling and pulling, and cooling and shaping to obtain a PET blister sheet.
[0024] Furthermore, in step three, the melt plasticization temperature is set to 200-220°C.
[0025] Beneficial effects of the present invention:
[0026] The present invention prepares fiber-reinforced components and functional rubber, and adds them into the preparation process of PET blister sheets to obtain PET blister sheets with excellent mechanical properties, impact resistance and antibacterial properties, with a tensile strength of up to 65.2MPa and an impact strength of up to 16.7KJ / m 2 , the antibacterial rate can reach 99.9%, which can achieve long-term antibacterial effect, avoid being eroded by bacteria, increase the service life of PET blister sheet, and broaden the application range of PET blister sheet.
[0027] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0029] Figure 1 The infrared spectrum of the fiber-reinforced component prepared by the present invention;
[0030] Figure 2 This is the infrared spectrum of the functional rubber prepared in the present invention. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] The preparation methods of the fiber-reinforced components and functional rubbers in the following examples and comparative examples are as follows:
[0033] 1. Preparation of fiber-reinforced components
[0034] Step SS1: 3.5 g of zirconia fiber was dispersed in N, N-dimethylformamide to form a uniform suspension, nitrogen was introduced for protection, 1.8 g of 4-chlorophthalic anhydride, 0.3 g of dicyclohexylcarbodiimide and 0.1 g of 4-dimethylaminopyridine were added to the suspension, mixed evenly, stirred for 5 h, filtered, washed and dried to obtain modified zirconia fiber;
[0035] Step SS2: Add 3 g of modified zirconia fiber to dimethyl sulfoxide, disperse evenly, introduce nitrogen protection, add 5.4 g of polycarbonate diol and 2 g of potassium carbonate, mix evenly, raise the system temperature to 75°C, react for 6 hours, separate the product, wash and dry to obtain a fiber-reinforced component.
[0036] The sample was prepared by potassium bromide tableting method, and the fiber-reinforced component was tested by infrared spectrometer, such as Figure 1 As shown in the figure, analysis shows that in the infrared spectrum of the fiber-reinforced component, 3026cm -1 The absorption peak of the CH bond in the benzene ring appeared at 1740 cm -1 The absorption peak of C=O in the ester group appeared at 1715 cm -1 The absorption peak of carboxyl C=O appeared at 1560 cm -1 、1412cm -1 The absorption peak of COO-Zr appeared at 1120 cm -1 The absorption peak of ether bond COC appeared at 740 cm -1 、558cm -1 The characteristic absorption peak of zirconia fiber appears at
[0037] 2. Preparation of functional rubber
[0038] Step A: 4.2 g of carboxyl-terminated polybutadiene acrylonitrile liquid rubber with a number average molecular weight of 2500 was added to dimethyl sulfoxide, and after stirring and mixing evenly, 2 g of dithiothreitol, 0.4 g of dicyclohexylcarbodiimide and 0.2 g of 4-dimethylaminopyridine were added, and after reacting for 5 hours, the product was separated to obtain a modified rubber;
[0039] Step B: Add 3.8 g of modified rubber to tetrahydrofuran, stir and mix evenly, introduce nitrogen protection, add 1.6 g of magnolol and 0.1 g of benzoin dimethyl ether, irradiate with an ultraviolet lamp with a wavelength of 352 nm and a power of 40 W in a dark environment, react for 2 hours, remove the solvent by reduced pressure distillation, and obtain a functional rubber.
[0040] The sample was prepared by potassium bromide tableting method, and the functional rubber was tested by infrared spectrometer using Fourier transform infrared spectrometer. Figure 2 As shown in the figure, analysis shows that in the infrared spectrum of functional rubber, 3220cm -1 The absorption peak of OH appeared at 3072 cm -1 The absorption peak of the CH bond in the carbon-carbon double bond appears at 3032 cm -1 The absorption peak of the CH bond in the benzene ring appeared at 2238 cm -1 The absorption peak of -CN appeared at 1731cm -1 The absorption peak of C=O in the ester group appeared at 1198 cm -1 The absorption peak of sulfide bond CSC appears at
[0041] Example 1
[0042] Preparation of PET blister sheet
[0043] Step 1: Add 75g of PET, 1g of ethylene-methyl acrylate-glycidyl methacrylate, 0.5g of zinc stearate, 5g of talc, 3g of fiber reinforcement component and 2g of functional rubber into a mixer, set the mixing temperature to 70°C, set the stirring rate to 100r / min, stir and mix for 20min to obtain a premixed base;
[0044] Step 2: melt-knead the premixed base material at 180° C., extrude and granulate to obtain a PET composite material;
[0045] Step 3: Add the PET composite material into a twin-screw extruder, perform melt plasticization, extrusion, rolling and pulling, and cooling and shaping at 200° C. to obtain a PET blister sheet.
[0046] Example 2
[0047] Preparation of PET blister sheet
[0048] Step 1: 80 g of PET, 2 g of ethylene-methyl acrylate-glycidyl methacrylate, 1 g of zinc stearate, 6 g of talc, 4 g of fiber reinforcement component and 3 g of functional rubber are added into a mixer, the mixing temperature is set to 80° C., the stirring rate is set to 200 r / min, and the mixture is stirred and mixed for 30 min to obtain a premixed base material;
[0049] Step 2: melt-knead the premixed base material at 200° C., extrude and granulate to obtain a PET composite material;
[0050] Step 3: Add the PET composite material into a twin-screw extruder, perform melt plasticization, extrusion, rolling and pulling, and cooling and shaping at 210° C. to obtain a PET blister sheet.
[0051] Example 3
[0052] Preparation of PET blister sheet
[0053] Step 1: 85 g of PET, 2.5 g of ethylene-methyl acrylate-glycidyl methacrylate, 1.5 g of zinc stearate, 7 g of talc, 5 g of fiber reinforcement component and 4 g of functional rubber were added into a mixer, the mixing temperature was set to 90° C., the stirring rate was set to 250 r / min, and the mixture was stirred for 40 min to obtain a premixed base material;
[0054] Step 2: melt-knead the premixed base material at 210° C., extrude and granulate, and obtain a PET composite material;
[0055] Step 3: Add the PET composite material into a twin-screw extruder, perform melt plasticization, extrusion, rolling and pulling, and cooling and shaping at 215° C. to obtain a PET blister sheet.
[0056] Example 4
[0057] Preparation of PET blister sheet
[0058] Step 1: Add 90g of PET, 3g of ethylene-methyl acrylate-glycidyl methacrylate, 2g of zinc stearate, 8g of talc, 6g of fiber reinforcement component and 5g of functional rubber into a mixer, set the mixing temperature to 100°C, set the stirring rate to 300r / min, stir and mix for 50min to obtain a premixed base;
[0059] Step 2: melt-knead the premixed base material at 220° C., extrude and granulate, and obtain a PET composite material;
[0060] Step 3: Add the PET composite material into a twin-screw extruder, perform melt plasticization, extrusion, rolling and pulling, and cooling and shaping at 220° C. to obtain a PET blister sheet.
[0061] Comparative Example 1
[0062] Preparation of PET blister sheet
[0063] Step 1: Add 80g of PET, 2g of ethylene-methyl acrylate-glycidyl methacrylate, 1g of zinc stearate, 6g of talc, and 4g of fiber reinforcement component into a mixer, set the mixing temperature to 80°C, set the stirring rate to 200r / min, and stir and mix for 30min to obtain a premixed base material;
[0064] Step 2: melt-knead the premixed base material at 200° C., extrude and granulate to obtain a PET composite material;
[0065] Step 3: Add the PET composite material into a twin-screw extruder, perform melt plasticization, extrusion, rolling and pulling, and cooling and shaping at 210° C. to obtain a PET blister sheet.
[0066] Comparative Example 2
[0067] Preparation of PET blister sheet
[0068] Step 1: Add 80g of PET, 2g of ethylene-methyl acrylate-glycidyl methacrylate, 1g of zinc stearate, 6g of talc, and 3g of functional rubber into a mixer, set the mixing temperature to 80°C, set the stirring rate to 200r / min, and stir and mix for 30min to obtain a premixed base;
[0069] Step 2: melt-knead the premixed base material at 200° C., extrude and granulate to obtain a PET composite material;
[0070] Step 3: Add the PET composite material into a twin-screw extruder, perform melt plasticization, extrusion, rolling and pulling, and cooling and shaping at 210° C. to obtain a PET blister sheet.
[0071] Comparative Example 3
[0072] Preparation of PET blister sheet
[0073] Step 1: Add 80g of PET, 2g of ethylene-methyl acrylate-glycidyl methacrylate, 1g of zinc stearate, 6g of talc, 4g of zirconium oxide fiber and 3g of functional rubber into a mixer, set the mixing temperature to 80°C, set the stirring rate to 200r / min, stir and mix for 30min to obtain a premixed base;
[0074] Step 2: melt-knead the premixed base material at 200° C., extrude and granulate to obtain a PET composite material;
[0075] Step 3: Add the PET composite material into a twin-screw extruder, perform melt plasticization, extrusion, rolling and pulling, and cooling and shaping at 210° C. to obtain a PET blister sheet.
[0076] Comparative Example 4
[0077] Preparation of PET blister sheet
[0078] Step 1: 80g of PET, 2g of ethylene-methyl acrylate-glycidyl methacrylate, 1g of zinc stearate, 6g of talc, 4g of fiber reinforcement component and 3g of magnolol were added into a mixer, the mixing temperature was set to 80°C, the stirring rate was set to 200r / min, and the mixture was stirred for 30min to obtain a premixed base;
[0079] Step 2: melt-knead the premixed base material at 200° C., extrude and granulate to obtain a PET composite material;
[0080] Step 3: Add the PET composite material into a twin-screw extruder, perform melt plasticization, extrusion, rolling and pulling, and cooling and shaping at 210° C. to obtain a PET blister sheet.
[0081] Performance Testing
[0082] The PET blister sheets prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were prepared into samples that met the test standards. The tensile strength of the samples was tested with reference to the standard GB / T 1040.2-2022 to evaluate the mechanical properties of the PET sheets. The impact strength of the samples was tested with reference to the standard GB / T1843-2008 to evaluate the impact resistance of the PET sheets.
[0083] After the samples were placed for 60 days, the antibacterial properties of the samples were tested using the following method: 2 mL of 10 -5 CFU / mL of Escherichia coli liquid was added to the surface of the sterilized sample, and cultured at 36℃ for 8h. 25μL of the liquid was evenly spread on the culture medium. After culturing at 36℃ for 24h, the number of colonies in the culture medium was counted as Q. A blank test was performed, and the number of colonies in the culture medium was counted as P. The antibacterial rate was calculated using the formula: Antibacterial rate (%) = [(PQ) / P] × 100%. The antibacterial properties of PET blister sheets were evaluated in this way. The test results are shown in the following table:
[0084]
[0085] It can be seen from the above table that the PET blister sheets prepared in Examples 1 to 4 of the present invention have excellent mechanical properties, impact resistance and antibacterial properties. Comparative Example 1 adds a fiber-reinforced component but does not add a functional rubber, and has excellent mechanical properties, but poor impact resistance and antibacterial properties; Comparative Example 2 adds a functional rubber but does not add a fiber-reinforced component, and has excellent impact resistance and antibacterial properties but poor mechanical properties; Comparative Example 3 adds zirconia fiber and functional rubber, and the zirconia fiber is directly added without modification, which may cause agglomeration and cannot cooperate with the polycarbonate diol, resulting in poor mechanical properties compared with the examples, but excellent impact resistance and antibacterial properties; Comparative Example 4 adds a fiber-reinforced component and magnolol, and has excellent mechanical properties, but magnolol is a small molecule that is easy to precipitate, resulting in a decrease in antibacterial properties, so the antibacterial properties are poor compared with the examples, and no flexible rubber segment is introduced, and the impact resistance is poor.
[0086] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A fiber-reinforced PET blister sheet, characterized in that: The invention comprises the following raw materials in parts by weight: 75-90 parts of PET, 1-3 parts of a compatibilizer, 0.5-2 parts of a lubricant, 5-8 parts of a filler, 3-6 parts of a fiber reinforcement component, and 2-5 parts of a functional rubber; The preparation method of the fiber-reinforced component comprises the following steps: Step SS1: Dispersing zirconium oxide fiber in N,N-dimethylformamide to form a uniform suspension, introducing nitrogen protection, adding a halogenated acid anhydride modifier, dicyclohexylcarbodiimide and 4-dimethylaminopyridine to the suspension, mixing evenly, stirring for 4-6 hours, filtering, washing and drying to obtain modified zirconium oxide fiber; the halogenated acid anhydride modifier is 3-chlorophthalic anhydride or 4-chlorophthalic anhydride; Step SS2: adding the modified zirconium oxide fiber to dimethyl sulfoxide, dispersing it uniformly, introducing nitrogen protection, adding polycarbonate diol and alkaline catalyst, mixing them uniformly, raising the system temperature to 70-80°C, reacting for 5-6 hours, separating the product, washing and drying it to obtain a fiber reinforcement component; the alkaline catalyst is potassium carbonate or sodium carbonate; The preparation method of the functional rubber is as follows: Step A: adding carboxyl-terminated polybutadiene acrylonitrile liquid rubber to dimethyl sulfoxide, stirring and mixing evenly, adding dithiothreitol, dicyclohexylcarbodiimide and 4-dimethylaminopyridine, reacting for 4-6 hours, separating the product to obtain a modified rubber; the number average molecular weight of the carboxyl-terminated polybutadiene acrylonitrile liquid rubber is 2500; Step B: adding the modified rubber to tetrahydrofuran, stirring and mixing evenly, introducing nitrogen protection, adding magnolol and a photoinitiator, irradiating with an ultraviolet lamp with a wavelength of 352nm and a power of 40W in a dark environment, reacting for 1-3h, removing the solvent by reduced pressure distillation, discharging, and obtaining a functional rubber; The photoinitiator is benzoin dimethyl ether or benzoin isopropyl ether.
2. A fiber-reinforced PET blister sheet according to claim 1, characterized in that: The compatibilizer is ethylene-methyl acrylate-glycidyl methacrylate; the lubricant is calcium stearate or zinc stearate; and the filler is talc powder or mica powder.
3. A fiber-reinforced PET blister sheet according to claim 1, characterized in that: The preparation method of the blister sheet comprises the following steps: Step 1: Add PET, compatibilizer, lubricant, filler, fiber reinforcement component and functional rubber into a mixer according to weight, set the mixing temperature to 70-100°C, set the stirring speed to 100-300r / min, stir and mix for 20-50min, and obtain a premixed base material; Step 2: Melt and knead the premixed base material at 180-220°C, extrude and granulate to obtain a PET composite material; Step 3: Add the PET composite material into a twin-screw extruder, perform melt plasticization, extrusion, rolling and pulling, and cooling and shaping to obtain a PET blister sheet.
4. A fiber-reinforced PET blister sheet according to claim 3, characterized in that: In step three, the melting and plasticizing temperature is set to 200-220°C.
Citation Information
Patent Citations
A PET composite material and its preparation method
CN108715674B
PET / PTT material reinforced by glass fiber and resisting bacterial with nanometer bamboo charcoal
CN104845132A
Multifunctional engineering plastic and production method thereof
CN117534945A